DI-088 Everolimus in tuberous sclerosis complex treatment - Gasque, MP Monforte; Fraile, R Rodil; Elizondo, M Castresana; Valencia, M Gutiérrez; Fabo, E Lacalle; González, J Fernández; Garrastatxu, I Monteserin; Uriz, M Etxeberria; Carricas, M Sarobe (European journal of hospital pharmacy. Science and practice, 2016)
BackgroundTuberous sclerosis complex (TSC) is an autosomal dominant disease with variable expressiveness and multisystem involvement. Everolimus, an mTOR inhibitor, is indicated for the treatment of kidney angiomyolipoma and subependymal giant cell astrocytoma (SEGA) associated with TSC.PurposeThe objectives of the study were to evaluate the effectiveness and safety of treatment in TSC.Material and methodsRetrospective observational study of patients treated with everolimus from July 2013 to April 2014.The collected variables were: sex, age, affected organs, dose, duration and reason for treatment.The effectiveness variables were, in each case: reduction in size of SEGA equal to or greater than 30%, reduction in size of the kidney angiomyolipomas in at least 25%, improvement of dyspnoea and/or absence of lung acute episodes.The safety profile of the drug was determined by the number of adverse reactions.Results4 patients were included:Patient No 1: female, 32 years old. Skin and neurological involvement. Everolimus was initiated at 7.5 mg four times daily for SEGA. No response to treatment was noted. Skin lesions disappeared and absence of epileptic seizures was observed. At the beginning of the treatment, the patient suffered grade 1 stomatitis.Patient No 2: female, 38 years old. Cerebral, skin, bone, heart and pulmonary involvement. Everolimus was initiated at 7.5 mg four times daily for pulmonary lymphangioleiomyomatosis. Response to treatment was achieved. There was also an improvement in osteomas and skin lesions. Grade 2 non-infectious pneumonitis was reported; this adverse event was resolved after dose reduction of everolimul to 5 mg four times daily.Patient No 3: male, 21 years old. Skin, ocular and neurological involvement. The treatment was initiated at 7.5 mg four times daily for SEGA. Reduction in size of SEGA of 30% was observed (response to treatment). At the beginning of the treatment the patient presented stomatitis and mild microalbuminuria (169 mg/g), which improved with enalapril treatment (63 mg/g).Patient No 4: female,15 years old. Skin, heart, kidney and brain involvement. Everolimus treatment was initiated at 10 mg four times daily due to kidney angiomyolipomas and SEGA. Neither response nor side effects were observed.Currently, all patients continue with the treatment; follow-up (median, range) is 17 (12–27) months.ConclusionEverolimus is the only well tolerated treatment for TSC, but its effectiveness is variable. In the cases where no response was observed, the lesions were stabilised.The number of patients is limited due to the low prevalence of this disease and to the restrictive criteria for initiating everolimus treatment.More studies are needed to determine the optimal dose and duration of treatment.No conflict of interest.